2014
DOI: 10.3390/atmos5020252
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Influence of Seasonal and Spatial Variations on the Estimation of Secondary Organic Carbon in Urban Particulate Matter by Applying the EC-Tracer Method

Abstract: Abstract:The elemental carbon (EC)-tracer method was applied to PM 10 and PM 1 data of three sampling sites in the City of Berlin from February to October 2010. The sites were characterized by differing exposure to traffic and vegetation. The aim was to determine the secondary organic carbon (SOC) concentration and to describe the parameters influencing the application of the EC-tracer method. The evaluation was based on comparisons with results obtained from positive matrix factorization (PMF) applied to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…Galindo et al [87] found annual-mean contributions (38%) of SOC to OC for PM 10 samples in urban Elche, Spain, whereas a 50% SOC fraction to OC mass of PM 2.5 and PM 10 samples was found in Lecce, Italy [88]. Conversely, estimated SOC concentrations of only 16-21% of OC mass in PM 10 samples were estimated at three sites in Berlin, Germany, for the BB-active period [89]. These findings indicate a north-south gradient in SOC contributions in Europe, related to climatic conditions favoring the generation or organic compounds that undergo gas-to-particle conversion.…”
Section: Determination Of Primary and Secondary Organic Carbonmentioning
confidence: 99%
“…Galindo et al [87] found annual-mean contributions (38%) of SOC to OC for PM 10 samples in urban Elche, Spain, whereas a 50% SOC fraction to OC mass of PM 2.5 and PM 10 samples was found in Lecce, Italy [88]. Conversely, estimated SOC concentrations of only 16-21% of OC mass in PM 10 samples were estimated at three sites in Berlin, Germany, for the BB-active period [89]. These findings indicate a north-south gradient in SOC contributions in Europe, related to climatic conditions favoring the generation or organic compounds that undergo gas-to-particle conversion.…”
Section: Determination Of Primary and Secondary Organic Carbonmentioning
confidence: 99%
“…Similarly to the North American continent, SOC estimates using the EC tracer method have been extensively performed throughout Europe [96,97,[122][123][124][125][126][127][128][129][130][131][132][133][134]. The annual and spring-summer average of SOC levels varied in the ranges 1.6-4.9 µgC m −3 and 0.90-4.4 µgC m −3 , contributing to 36-73% and 41-84% of PM 2.5 OC, respectively (Figures 2 and 3, Tables SA2 and SA3).…”
Section: Europe and The Middle Eastmentioning
confidence: 99%